Can procalcitonin measurement help the diagnosis of osteomyelitis and septic arthritis? A prospective trial - Faesch Sabine; Cojocaru Bogdan; Hennequin Carole; Pannier Stéphanie; Glorion Christophe; Lacour Bernard; Chéron Gérard (BMC, 2009)
Abstract Objectives Procalcitonin (PCT) is an accurate marker for differentiating bacterial infection from non-infective causes of inflammation or viral infection. However, there is only one study in children which tested procalcitonin as a diagnostic aid in skeletal infections. With this study we sought to evaluate the sensitivity, specificity and predictive values of procalcitonin for identifying bone and joint infection in children evaluated in the emergency department for non traumatic decreased active motion of a skeletal segment. Methods Patients aged 1 month to 14 years were prospectively included in the emergency department when suspected for osteomyelitis or septic arthritis. Procalcitonin levels, C reactiv protein, white blood cell count were measured and bacteriological samples were collected before initiation of antibiotic treatment. Patients were assigned to 3 groups according to the degree of suspected infection: group 1 confirmed infection, group 2 presumed infection and group 3 non infected patients. Results Three hundred thirty nine patients were included (118 girls and 221 boys). Group 1 comprised 8 patients (2 had PCT levels > 0.5 ng/ml). Two had osteomyelitis and 6 septic arthritis. Forty children were incuded in group 2 (4 had PCT levels > 0.5 ng/ml). Eighteen had presumed osteomyelitis and 22 presumed septic arthritis. Group 3 comprised 291 children (9 PCT levels > 0.5 ng/ml) who recovered without antibiotic treatment. The specificity of the PCT as a marker of bacterial infection (comparing Group 1 and Group 3) was 96.9% [95% CI, 94.2-98.6], the sensitivity 25% [95% CI, 3.2-65.1], the positive predictive value (PPV) 18.2% [95% CI, 2.3-51.8] and the negative predictive value (NPV) 97.9% [95% CI, 95.5-99.2]. Conclusion PCT is not a good screening test for identifying skeletal infection in children. Larger studies are needed to evaluate still more the place of PCT measurements in the diagnosis of osteomyelitis and septic arthritis.